Data: Effect of substrate alloy type on the hardness profile of the substrate and deposited material interface in Aluminium Wire + Arc Additive Manufacturing - Eimer, Eloise (Cranfield University, 2023)
This file provides the hardness measurements used in the paper to plot the different hardness profiles in figures 3 and 9 and the chemical composition measurement displayed in figure 10.
Keywords: 'Additive manufacturing'; 'Directed Energy Deposition'; 'Wire and Arc Additive Manufacturing'; 'Additive Manufacturing'; 'Metals and Alloy Materials'